The North American Industry Classification System and Its Implications for Accounting Research* - Krishnan, Jayanthi; Press, Eric (Contemporary Accounting Research, 2003)
Abstract Industry classification is an important component of the methodological infrastructure of accounting research. Researchers have generally used the Standard Industrial Classification (SIC) system for assigning firms to industries. In 1999, the major statistical agencies of Canada, Mexico, and the United States began implementing the North American Industry Classification System (NAICS). The new scheme changes industry classification by introducing production as the basis for grouping firms, creating 358 new industries, extensively rearranging SIC categories, and establishing uniformity across all NAFTA nations. We examine the implications of the change for accounting research. We first assess NAICS's effectiveness in forming industry groups. Following Guenther and Rosman 1994, we use financial ratio variances to measure intra‐industry homogeneity and find that NAICS offers some improvement over the SIC system in defining manufacturing, transportation, and service industries. We also evaluate whether NAICS might have an impact on empirical research by reproducing part of Lang and Lundholm's 1996 study of information‐transfer and industry effects. Using SIC delineations, they focus on whether industry conditions or the level of competition is the main source of uncertainty resolved by earnings announcements. Across all levels of aggregation, we find inferences are similar using either SIC or NAICS. How‐ever, we also observe that the regression coefficients in Lang and Lundholm's model show smaller intra‐industry dispersion for NAICS, relative to SIC, definitions. Overall, the results suggest that NAICS definitions lead to more cohesive industries. Because of this, researchers may encounter some differences in using NAICS‐industry definitions, rather than SIC, but these will depend on research design and industry composition of the sample.